Controlling and Monitoring Stem Cell Safety In Vivo in an Experimental Rodent Model. (November 2014) - Leten, Cindy; Roobrouck, Valerie D.; Struys, Tom; Burns, Terry C.; Dresselaers, Tom; Vande Velde, G.; Santermans, Jeanine; Nigro, Antonio Lo; Ibrahimi, Abdelilah; Gijsbers, Rik; Eggermont, Kristel; Lambrichts, Ivo; et al.
Abstract Adult stem cells have been investigated increasingly over the past years for multiple applications. Although they have a more favorable safety profile compared to pluripotent stem cells, they are still capable of self‐renewal and differentiate into several cell types. We investigated the behavior of Oct4‐positive (Oct4+) and Oct4‐negative (Oct4−) murine or rat bone marrow (BM)‐derived stem cells in the healthy brain of syngeneic mice and rats. Engraftment of mouse and rat Oct4‐positive BM‐derived hypoblast‐like stem cells (m/rOct4+ BM‐HypoSCs) resulted in yolk‐sac tumor formation in the healthy brain which was monitored longitudinally using magnetic resonance imaging (MRI) and bioluminescence imaging (BLI). Contrast enhanced MRI confirmed the disruption of the blood brain barrier. In contrast, m/r Oct4‐negative BM‐derived multipotent adult progenitor cells (m/rOct4− BM‐MAPCs) did not result in mass formation after engraftment into the brain. mOct4+ BM‐HypoSCs and mOct4− BM‐MAPCs were transduced to express enhanced green fluorescent protein, firefly luciferase (fLuc), and herpes simplex virus‐thymidine kinase to follow up suicide gene expression as a potential "safety switch" for tumor‐forming stem cells by multimodal imaging. Both cell lines were eradicated efficiently in vivo by ganciclovir administration indicating successful suicide gene expression in vivo, as assessed by MRI, BLI, and histology. The use of suicide genes to prevent tumor formation is in particular of interest for therapeutic approaches where stem cells are used as vehicles to deliver therapeutic genes. Stem Cells2014;32:2833–2844